Kartu Braille Bertanya As A Learning Medium For Visually Impaired Children - Nurhanisa, Nisha; Arafah, Salsa Billa; Pawitra, Balerina Aulia; Kamila, Intan Rahma; Sudana, Undang (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2023)
A good learning process will have an impact on good results too. Good learning must of course be supported by adequate facilities or teaching media that are in line with students' needs. Especially for students with disabilities who have limitations, one of the disabled people with physical limitations is the blind, namely children who have problems with their sense of sight. In Indonesia, quite a few special schools still lack varied learning facilities, one of which is in Cicalengka, more precisely at SLB A YPKR Cicalengka. The lack of facilities for learning while playing at Special Schools causes students to be less than optimal in the learning process. The focus of this activity is blind students and teachers at SLB A YPKR Cicalengka. Cards written in braille which can also be called “Kartu Braille Bertanya” are a medium for students and teachers to carry out interactive learning activities. These “Kartu Braille Bertanya” help teachers to guide students through exciting learning and more varied learning, from reading, speaking and expressing feelings.